Species diversity of reptiles in Palpa District, Nepal - Nepali, Pit Bahadur; Singh, Nanda Bahadur (Nepalese Journal of Zoology, 2022)
Gastrointestinal (GI) This study was conducted in agricultural field, forests, riparian and wetland habitats, and human habitats of six sampling sites in Palpa, Nepal, from May 2016 and April 2020. The purpose of the study was to document and measure the richness, abundance, and diversity of the reptile in this district. Data was collected randomly in these habitats of this district using quadrat, visual encounter, and opportunistic survey methods. For 100 quadrates for each site seasonally, 20 quadrats were placed in each habitat along 5 transects. In total, 554 individual species belonging to 9 families, 26 genera, and 34 species were recorded. The richness of reptiles species was high in the human habitat and forest (S= 25) but lower in wetland (S=6). The abundance was more in human habitat than in other habitats. Shannon diversity index (Hˈ) of reptile was 2.51 and 0.99 in forest and wetland respectively. Similarly, the Simpson index in reptiles (λ) was high in forest (0.87) and low in wetland (0.57). Pielou evenness (J) of individuals among the species was 0.29 in forest and 0.54 in wetland. The values indicate that the diversity of reptiles was higher in forest as compared to the wetland. This study aids the resources for additional research.